Oxygen K-edge electron energy loss spectra of hydrous and anhydrous compounds. - Winkler, B; Avalos-Borja, M; Milman, V; Perlov, A; Pickard, C; Yates, JR (2013)
First-principles calculations have been employed to examine the possible use of electron energy loss spectroscopy (EELS) as a tool for determining the presence of OH groups and hence hydrogen content in compounds. Our density functional theory (DFT) based calculations describe accurately the experimental EELS results for forsterite (Mg2SiO4), hambergite (Be2BO3(OH)), brucite (Mg(OH)2) and diaspore (α-AlOOH). DFT calculations were complemented by an experimental time resolved study of the oxygen K-edge in diaspore. The results show unambiguously that there is no connection between a pre-edge feature in the oxygen K-edge spectrum of diaspore and the presence of OH groups in the structure. Instead, the experimental study shows that the pre-edge feature in diaspore is transient. It can be explained by the presence of molecular O2, which is produced as a result of the electron irradiation.